Optimal Sizing and Locations of Multiple BESSs in Distribution Systems Using Crayfish Optimization Algorithm - Wichitkrailat, Krit; Premrudeepreechacharn, Suttichai; Siritaratiwat, Apirat; Khunkitti, Sirote (IEEE access, 2024)
In distribution systems, battery energy storage systems (BESSs) are the key to fully utilize energy generated from all installed distributed generations (DGs). Only one BESS might be inadequate for present distribution systems connected with several DGs. Thus, this work presents the optimal sizing and locations of multiple BESSs in distribution systems connected with distributed generations (DGs) where more than one BESS is investigated. To solve the complicated problem with multiple BESSs, a newly proposed optimization algorithm named crayfish optimization algorithm (COA) is applied to solve the problem, and the results are compared with those generated from particle swarm optimization (PSO) and salp swarm algorithm (SSA). The optimization problem aims to minimize overall system costs while enhancing distribution system performance in three aspects including voltage regulation improvement, peak demand reduction, and power loss reduction. The IEEE 33- and 69-bus distribution systems connected with DGs are tested to verify the approach. The simulation results demonstrate that BESS installations can significantly improve the efficiency of the distribution systems where installing multiple BESSs proves to be more effective than a single BESS although it also increases the overall costs. It is found that in the case of multiple BESSs, %VDI, peak demand, and power loss could be improved from the base case by 43.43%, 50.00%, and 12.21%, respectively, in the IEEE 33-bus system and 42.32%, 45.74%, and 4.69%, respectively, for the IEEE 69-bus system. Furthermore, it is found that COA outperforms the compared algorithms in both systems.